Risk factors of early neonatal death in East Nusa Tenggara, Indonesia: a case-control study - Irene K.L.A. Davidz; Kuntoro Kuntoro; Hermanto T. Joewono; Irwanto Irwanto (Paediatrica Indonesiana, 2022)
Background The neonatal mortality in East Nusa Tenggara is still high, contributes up to 75% of all neonatal death and more than 70% of early neonatal death which occurred less than 7 days after birth.. Objective This study aimed to analyze the risk factors of early neonatal death in East Nusa Tenggara. Methods This case control study was conducted in 18 districts of East Nusa Tenggara, Indonesia. The case was newborn death, while the control was alive newborn during the early neonatal period. The data was obtained from the maternal and neonatal medical record that was kept in provincial health office and each health district office. An interview with mothers was performed if needed. The observed variables were the early neonatal death as a dependent variable and various independent variables. Results The early neonatal death was associated with maternal age under 20 or over 35 years old (OR=1.8; 95%CI 1.1 to 3.1; P=0.032), the history of stillbirth (OR=27.5; 95%CI 11.6 to 64.5; P=0.000), mother with tuberculosis (OR=15.3; 95%CI 1.7 to 137.3; P=0.015), mother with hyperthyroid (OR=15.5; 95%CI 2.2 to 107; P=0.006), the risk for premature labor (OR= 4.5; 95%CI 2.3 to 8.7; P=0.000), prolonged labor (OR=2.3; 95%CI 1.2 to 4.8; P=0.020), the delivery not in a health facility (OR=18.6; 95%CI= 6.5 to 52.7; P=0.000), low birth weight infants (OR=5.6; 95%CI 3 to 10.3; P=0.000), and asphyxia (OR=25.2; 95%CI 95% 9.9 to 64.5; P=0.000). Conclusions Increased early neonatal death is associated with maternal age, history of stillbirth, mother with hyperthyroid or tuberculosis, prolonged or risk for premature labor, delivery not in a health facility, low birth weight infants, and asphyxia.